Differences in the Thoracic Aorta by Region and Sex in a Murine Model of Marfan Syndrome - Jiménez-Altayó, Francesc; Siegert, Anna-Maria; Bonorino, Fabio; Meirelles, Thayna; Barberà, Laura; Dantas, Ana P.; Vila, Elisabet; Egea, Gustavo (Frontiers in Physiology, 2017)
Marfan syndrome (MFS) is a hereditary disorder of the connective tissue that causes life-threatening aortic aneurysm, which initiates at the aortic root and can progress into the ascending portion. However, analysis of ascending aorta reactivity in animal models of MFS has remained elusive. Epidemiologic evidence suggests that although MFS is equally prevalent in men and women, men are at a higher risk of aortic complications than non-pregnant women. Nevertheless, there is no experimental evidence to support this hypothesis. The aim of this study was to explore whether there are regional and sex differences in the thoracic aorta function of mice heterozygous for the fibrillin 1 (Fbn1) allele encoding a missense mutation (Fbn1C1039G/+), the most common class of mutation in MFS. Ascending and descending thoracic aorta reactivity was evaluated by wire myography. Ascending aorta mRNA and protein levels, and elastic fiber integrity were assessed by qRT-PCR, Western blotting, and Verhoeff-Van Gieson histological staining, respectively. MFS differently altered reactivity in the ascending and descending thoracic aorta by either increasing or decreasing phenylephrine contractions, respectively. When mice were separated by sex, contractions to phenylephrine increased progressively from 3 to 6 months of age in MFS ascending aortas of males, whereas contractions in females were unchanged. Endothelium-dependent relaxation was unaltered in the MFS ascending aorta of either sex; an effect related to augmented endothelium-dependent hyperpolarization-type dilations. In MFS males, the non-selective cyclooxygenase (COX) inhibitor indomethacin prevented the MFS-induced enhancement of phenylephrine contractions linked to increased COX-2 expression. In MFS mice of both sexes, the non-selective nitric oxide synthase inhibitor L-NAME revealed negative feedback of nitric oxide on phenylephrine contractions, which was associated with upregulation of eNOS in females. Finally, MFS ascending aortas showed a greater number of elastic fiber breaks than the wild-types, and males exhibited more breaks than females. These results show regional and sex differences in Fbn1C1039G/+ mice thoracic aorta contractility and aortic media injuries. The presence of more pronounced aortic alterations in male mice provides experimental evidence to support that male MFS patients are at increased risk of suffering aortic complications.